2000
DOI: 10.23986/afsci.5665
|View full text |Cite
|
Sign up to set email alerts
|

Seed production characters and germination performance of reed canary grass in Finland

Abstract: Production of reed canary grass (Phalaris arundinacea L.) seed in Finland may be of interest in the near future. Seed production characters of cultivars Palaton and Venture were studied between 1995 and 1998 at Jokioinen. Effects of harvest time on seed yield, thousand seed weight and seed germination were evaluated for 'Palaton'. Seed yield varied from 2 to 432 kg ha-1, being only 100 kg ha-1 on average. In the years of highest seed yields the optimum harvest time was 15 days after complete anthesis. At that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 11 publications
(7 reference statements)
2
7
0
1
Order By: Relevance
“…According to results from this study cultivars had a later optimal time of harvest (16–18 DAA) than breeding lines and wild populations (11–13 DAA). Results of a previous study (Sahramaa and Hömmö, 2000) also supported this finding, which indicated the best harvest time for cultivar Palaton to be 15 DAA. In general, the later the harvest the lower the seed yield and panicle weight and the higher the seed shattering.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…According to results from this study cultivars had a later optimal time of harvest (16–18 DAA) than breeding lines and wild populations (11–13 DAA). Results of a previous study (Sahramaa and Hömmö, 2000) also supported this finding, which indicated the best harvest time for cultivar Palaton to be 15 DAA. In general, the later the harvest the lower the seed yield and panicle weight and the higher the seed shattering.…”
Section: Discussionsupporting
confidence: 70%
“…Bonin and Goplen (1966) reported heritability of seed yield components, and Jonassen (1994) detailed effects of various treatments on seed yield. Baltensperger and Kalton (1958)(1959) and Bonin and Goplen (1963) reported variability in seed shattering, Landgraff and Junttila (1979), Junttila and Nilsen (1980), and Berg (1992) studied variation in seed germination and seed dormancy, and Sahramaa and Hömmö (2000) recorded variation in seed production in Finland.…”
mentioning
confidence: 99%
“…Seed shattering and yield both depend on environmental conditions (Hermann 1975 ;Sahramaa and Hömmö 2000 ). Seed shattering and yield both depend on environmental conditions (Hermann 1975 ;Sahramaa and Hömmö 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Na problémy s často i extrémně nízkou klíčivostí semen této trávy upozorňuje například Wheaton (1993). Sahramaa a Hömmö (2000) odůvodňují nízkou klíčivost nerovnoměrným dozráváním semen této trávy či špatně zvoleným termínem sklizně. V rychlosti klíčení vynikal druh Elymus elongatus, jehož semena začala klíčit vždy po 3 dnech od založení pokusu.…”
Section: Výsledky a Diskuseunclassified